2019
DOI: 10.1590/0047-2085000000245
|View full text |Cite
|
Sign up to set email alerts
|

Prevalência de comportamentos de risco para transtornos alimentares e uso de dieta “low-carb” em estudantes universitários

Abstract: RESUMO Objetivos Identificar a presença de compulsão alimentar associada ou não a práticas compensatórias em praticantes de dieta low-carb. Métodos Foram utilizadas a Escala de Compulsão Alimentar Periódica (ECAP) e o Questionário de Hay para avaliar a frequência de compulsão alimentar e práticas compensatórias, além de um questionário de frequência do consumo de chocolate, pão e arroz. A intensidade de restrição de carboidratos foi avaliada com escala de 1 a 8 pontos. Os participantes foram divididos nos … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 30 publications
0
7
0
6
Order By: Relevance
“…The adapted questionnaire was previously validated for its reliability, which indicated that it could be more effective in investigating less frequent behaviors (Ferreira and Da Veiga, 2008). It has already been adopted in Brazilian investigations with a similar population to our study (de Carvalho et al, 2017;Pena Gralle et al, 2017;De Oliveira et al, 2019;de Matos et al, 2021). Three risk behaviors for eating disorders were evaluated using this scale, namely: binge eating (the act of ingesting large amounts of food at once with the feeling of loss of control at the time of ingestion), purgative (use of laxatives, diuretics, or self-induced vomiting), and food restriction (fasting or restrictive diet).…”
Section: Methodsmentioning
confidence: 99%
“…The adapted questionnaire was previously validated for its reliability, which indicated that it could be more effective in investigating less frequent behaviors (Ferreira and Da Veiga, 2008). It has already been adopted in Brazilian investigations with a similar population to our study (de Carvalho et al, 2017;Pena Gralle et al, 2017;De Oliveira et al, 2019;de Matos et al, 2021). Three risk behaviors for eating disorders were evaluated using this scale, namely: binge eating (the act of ingesting large amounts of food at once with the feeling of loss of control at the time of ingestion), purgative (use of laxatives, diuretics, or self-induced vomiting), and food restriction (fasting or restrictive diet).…”
Section: Methodsmentioning
confidence: 99%
“…Practice of Low-Carb Diet and Intermittent Fasting. Participants were asked about their practice and frequency of LC diet and IF [ 2 ], using the following questions: (a) In the last three months, have you tried to be on a low-carb diet, avoiding foods that are sources of carbohydrate? (“yes”, “no” and “I do not know what a low-carb diet is”); (b) Considering the previous question, in the last three months, how many times in a week have you had intermittent fasting?…”
Section: Methodsmentioning
confidence: 99%
“…Recent evidence points out that it has deleterious effects, especially in developing disordered eating, defined as problematic eating behaviors used to lose or control. [ 1 ] Evidence shows that disturbed eating behaviors are more frequent in individuals with body concerns and body dissatisfaction, making them at greater risk of developing eating disorders (ED) [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, we have seen a large increase in EDs in the population, and the progress of nutrition science coupled with the growth of nutritionism in popular discourses have been influencing the "search for health" by rigid means, sometimes called lifestyle [29]. In 2019, we found that 25% of university students had practiced a low-carb diet [30]. Within the group that carried out the diet, 35% associated with Intermittent Fasting (a practice spread by the simplification of the science of nutrition combined with lifestyle).…”
mentioning
confidence: 99%